2012
DOI: 10.2478/v10181-011-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic and proteolytic activity of coagulase-negative staphylococci isolated from mastitis cows

Abstract: The aim of the present study was to assess the haemolytic and proteolytic activity of coagulase-negative staphylococci (CNS) isolated from cows with mastitis. The study was conducted on 100 CNS strains: S. xylosus (n=28), S.chromogenes (n=26), S.haemolyticus (n=25), S. sciuri (n=14), S. warneri (n=4), S.hominis (n=2), S.saprophyticus (n=1); 22 CNS were isolated from cows with clinical mastitis and 78 from those with subclinical mastitis. The CNS studied showed the ability to produce only α-haemolysin and belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Staphylococcus equorum, S. warneri and S. lentus are less frequently present in such material according to the literature data (Anaya-López et al 2006, Bochniarz et al 2012. The available literature fails to offer data concerning subclinical infections in the udders of cows caused by S. vitilinus, even though in the present study these microorganisms were identified by MALDI-TOF MS in 15% of the disease cases.…”
Section: Discussionmentioning
confidence: 51%
“…Staphylococcus equorum, S. warneri and S. lentus are less frequently present in such material according to the literature data (Anaya-López et al 2006, Bochniarz et al 2012. The available literature fails to offer data concerning subclinical infections in the udders of cows caused by S. vitilinus, even though in the present study these microorganisms were identified by MALDI-TOF MS in 15% of the disease cases.…”
Section: Discussionmentioning
confidence: 51%
“…The pathogenicity of staphylococci is related to the production of several virulence factors responsible for the development of disease process ( factors were found in S. aureus strains isolated from bovine mastitis (Silva et al 2005, Hata et al 2006, Peles et al 2007, Melchior et al 2009, Capurro et al 2010, but only few studies involved search of virulence factors of CNS isolated from bovine mastitis (Zhang andMaddox 2000, Bochniarz andWawron 2012). Virulence factors of staphylococci have been investigated by measuring phenotypic expression of products associated with virulence (Taponen and Pyörälä 2009).…”
Section: Discussionmentioning
confidence: 99%
“…CNS strains isolated from milk of cows with mastitis produced proteases and haemolysins (Zhang andMaddox 2000, Bochniarz andWawron 2012). Moreover, biofilm formation has been proposed as an important virulence factor of CNS, by which mastitis-causing staphylococci avoid the immune response of the cow and cause persistent intramammary infections (Simojoki et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the present work the presence of the mecA gene was investigated by PCR, the incidence of methicillin resistance in the tested MRCoNS was 50% [3/6] by the presence of mecA gene, as shown in Table [ 4] and Fig. [3].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic mechanisms of CoNS are expressed by two parameters: invasiveness [ability to permeate through protective barriers, to adhere to host cells and to form a biofilm] and toxicity [capacity to produce enzymes and toxins, including haemolysins and proteases], [4] .…”
Section: Introductionmentioning
confidence: 99%